Grafting dan Okulasi: Strategi Efektif untuk Perbanyakan Tanaman Berkualitas Tinggi - Nashwa Intana Putri; Nurin Fatnata; Puput Fuji Aslamiah; Raden Elfa; Rifa Musyaropah; Ita Fitriyyah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Vegetative propagation is an effective method for producing high quality plant seeds with similar characteristics to the parent plant. Techniques such as grafting and grafting are used to accelerate growth and increase plant resistance to pests and diseases. The advantages of this method compared to generative propagation include a faster fruiting period and consistency in the aroma and taste of the fruit. This research also highlights the importance of genetic compatibility between rootstock and scion and the use of phytohormones in the success of vegetative propagation techniques. The results show that both techniques can increase plant productivity, speed up fruiting time, and produce plants that are stronger and more adaptive to environmental conditions